USM STUDENTS ENGAGE IN COMMUNITY OUTREACH WORK IN LAOS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 26 May 2016 – Students from Universiti Sains Malaysia (USM) had the opportunity to meet with the community from Laos recently through the 'International Malaysia-Laos Youth Exchange and Study Programme 2016' for 3 days from 7 May 2016.